2020
DOI: 10.1017/s0022215119002652
|View full text |Cite
|
Sign up to set email alerts
|

The role of smartphone applications in clinical practice: a review

Abstract: ObjectiveThe number of medical mobile phone applications continues to grow. Although otorhinolaryngology-specific applications represent a small proportion, there are exciting innovations emerging for the specialty. This article will assess the number of applications available and review how they may be used in clinical practice.MethodThe application stores of the two most popular mobile phone platforms, Apple and android, were searched using multiple search terms.ResultsA total of 107 ENT applications were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…These included well-known dictionary applications (like Oxford, Merriam Webster, and Google Translate), YouTube channels (Loukgolf's English Room and music videos with lyrics), and other applications found were more general and discursive (BBC Learning English TED Talk). Others included those used in the medical field like ell Scope Lite, Digital Otoscope, FireflyPro Mobile and iScope (Wallace and Kanegaonkar 2020).…”
Section: Mobile Phone Learning Applicationsmentioning
confidence: 99%
“…These included well-known dictionary applications (like Oxford, Merriam Webster, and Google Translate), YouTube channels (Loukgolf's English Room and music videos with lyrics), and other applications found were more general and discursive (BBC Learning English TED Talk). Others included those used in the medical field like ell Scope Lite, Digital Otoscope, FireflyPro Mobile and iScope (Wallace and Kanegaonkar 2020).…”
Section: Mobile Phone Learning Applicationsmentioning
confidence: 99%
“…and they offer key information for the screening and characterization of voice pathology associated with a lesion or functional alteration of the vocal cords. Despite being a recent tool, the Voice Clinical Systems is included in the list of validated applications for smartphones for clinical practice [8] . In addition, various investigations have shown the effectiveness of this tool for screening patients with vocal pathology [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, there are a few studies indicating health professionals and users who participated in the design and development of such mHealth apps, and many did not describe the theoretical frameworks adopted to achieve behavior change. [18][19][20] This means that many of them may not be effective in terms of achieving the benefits and purpose for which it has been developed. 21 There is limited evidence on the economic impact of HAIs in Brazil, a very recent Brazilian study about the occupation-day total average costs per patient with HAI concluded that the daily cost of a patient with HAI was 55% higher than that of a patient without a HAI.…”
mentioning
confidence: 99%